Unveiling microbial dynamics in terasi spontaneous fermentation: Insights into glutamate and GABA production - Gemilang Lara Utama; Novia Rahmah Maulani Sahab; Siti Nurmilah; Vira Putri Yarlina; Edy Subroto; Roostita L. Balia (Current Research in Food Science, 2025)
Terasi, a traditional Indonesian seafood product made from shrimp, undergoes fermentation facilitated by a consortium of microorganisms, including Lactic Acid Bacteria (LAB) and yeast, which contribute to its distinctive umami flavor. This study investigates the microbial dynamics and production of key metabolites, including γ-aminobutyric acid (GABA), during terasi fermentation. Total Plate Count (TPC) and High-Performance Liquid Chromatography (HPLC) were used to monitor changes in glutamate and GABA levels, with glutamate increasing from 105.18 mg/mL on day 3–139.19 mg/mL on day 14, and GABA rising from 90.49 mg/mL to 106.98 mg/mL over the same period. Metagenomic analysis using high-throughput sequencing of bacterial 16 S rRNA identified Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidota as dominant phyla. While LAB populations remained relatively stable, yeast became detectable from day 4. Notably, core bacterial genera such as Vibrio, Macrococcus, Staphylococcus, Exiguobacterium, Jeotgalicoccus, Prevotella, Salinicoccus, Bacillus, Pseudarthrobacter, and Vagococcus were highly abundant and played significant roles in GABA production, likely due to their glutamate decarboxylase activity. These findings reveal a clear correlation between microbial succession and metabolite production, offering valuable insights into the fermentation process of terasi. This study enhances the understanding of traditional food fermentation and presents opportunities to optimize beneficial compounds in terasi products.